A Privacy-preserving Opportunistic Computing Framework for Mobile-Healthcare Emergency - Mishra, Supriya; Shukla, Sohit (IJRDO -Journal of Computer Science Engineering, 2016)
Nowadays the quality of healthcare has been improved gradually. However, the time consuming pre-hospital emergency process could sometimes cause many regrets. Therefore, the minimization of time required for providing primary care and consultation to patients is one of the crucial factors when trying to improve the healthcare delivery in emergency situations. If the Emergency Medical Technician (EMT) can hold on signs of life of patients immediately when accidents happened, higher quality of healthcare could be achieved. Mobile healthcare is a new paradigm that combines the evolution of emerging wireless communications and network technologies to connect healthcare anytime and anywhere. The purpose of the study is to develop a Mobile Emergency Healthcare Information System (MEHIS). A Standard Operation Procedure of Emergency Healthcare (SOPEH) is first planned. Then, the system is developed for EMT or families of patients to communicate with physicians in hospitals. Users can use their 3G mobile phone to transfer symptoms and information of the situation to JSP server which then quickly delivers information while providing proper emergency care at the prime time. Meanwhile, MEHIS can shorten emergency healthcare time and therefore enhance quality of emergency healthcare.